Kajian Teknis Geometri Jalan Angkut Batubara Menuju Pelabuhan Khusus Milik PT Baturona Adimulya Untuk Mencapai Target Produksi - Febrian Syukra; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Coal transportation is important in achieving coal production targets. The condition of road geometry is one of the factors that influence transportation activities. The purpose of this research is to conduct a technical study of the geometry of the coal haul road from the Sumatra Jambi-Palembang crossroads to the special port owned by PT Baturona Adimulya to achieve the coal production target. The study was conducted by direct observation to the field to obtain primary data and secondary data needed. The results of the data analysis show that the geometry of the mining road still needs to be improved in certain segments. The actual condition of the width of the B-C (bend) and E-F (straight) segments of 10.6 m and 8.5 meters wide is not yet ideal, so it is necessary to increase the width of the road respectively in the width of 0.7 meters and 0.5 meters. The actual slope of the road in all segments is ideal. The actual superelevation of the F-G segment valued at 0.29 m is not ideal yet, so the elevation outside the bend needs to be added at 0.15 meters. The actual cross slope, segments A-B and E-F, respectively 10 cm and 15 cm, are not yet ideal, so it is necessary to add height to the middle of each segment as high as 8 cm and 3 cm. Production of conveyance before repairing was 56.2948.98 tons and after repairing the road geometry was 60.144.92 tons.Keywords: Transportation Geometry, Improvement Plan, Production Target, Cycle Time, Technical Study